1 kW average power emission from an in-house 4x4 multicore rod-type fiber - Klenke, Arno; Steinkopff, Albrecht; Aleshire, Christopher; Jauregui, Cesar; Kuhn, Stefan; Nold, Johannes; Haarlammert, Nicoletta; Schreiber, Thomas; Tuennermann, Andreas; Limpert, Jens (2021 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2021, 2021)
Multicore fibers have the potential to combine the advantages of optical fibers (such as their high average power capability, high efficiency and well-defined beam quality) with those stemming from the large beam areas commonly used in other laser architectures. Coherent combination can then be employed to achieve one single, high-quality, output beam [1] , [2]. To match and even surpass the performance of state-of-the-art lasers systems comprising multiple separate fiber amplifiers, multicore fibers need to leverage the same technological advancements. One example is the use of a rod-type geometry with large core diameters to mitigate detrimental nonlinear effects. In this contribution, we present our high power laser results achieved with an in-house, all-glass, rod-type multicore fiber, whose basic structure is shown in figure 1. The fiber contains 16 ytterbium-doped cores in a rectangular arrangement with a diameter of 22m each, operating at near single-mode output. The core-to-core pitch is 58m. An embedded octagonal fluoride ring is used as the guiding mechanism for the pump with a diameter of 310m and a NA of 0.22. A device length of 1.1 m was chosen to provide sufficient pump absorption.
CRIS-Team Scopus Importer:2023-04-20